Inelastic Displacement Spectra and Its Utilization of DDB Design for Seismic Isolated Bridges Subjected to Near-Fault Pulse-Like Ground Motions. Issue 3 (August 2019) - Wu, Yi-feng; Wang, Hao; Li, Jian; Sha, Ben; Li, Ai-qun
A variety of research has focused on the inelastic displacement demand of a single degree of freedom (SDOF) system when subjected to near-fault pulse-like ground motions, in which the concerned ductility, μ, is typically lower than ten for normal structures. However, for seismic isolated structures that are more prone to large displacement, the corresponding research is limited. The purpose of this paper is to investigate the inelastic displacement spectra of an SDOF system with μ ranging from 5 to 70 and further proposes a direct displacement-based (DDB) design method for seismic isolated bridges. More concretely, a pool of near-fault pulse-like records is assembled, the mean C μ as a function of T / T p is developed, and the influences of the ductility, μ, and the post-to-pre-yield ratio, α, on C μ are carefully investigated. Then the corresponding inelastic displacement spectra, S d, are obtained, and a comprehensive piecewise expression is proposed to fit S d . After that, the utilization of the spectra for the DDB design of a three-span seismic isolated continuous bridge is performed, and the principal of simplifying the bridge to an SDOF system is carefully explained and verified.